ANALISIS KETERSEDIAAN AIR IRIGASI DAN MODEL POLA TANAM DALAM PENGEMBANGAN POTENSI LAHAN PERTANIAN PADI SAWAH DI KABUPATEN KONAWE - Jasman Jasman (Yayasan Akrab Pekanbaru, 2019)
In terms of quantity, the problem of water for agriculture, especially in dry land, is the incompatibility of water distribution between needs and supply according to time (temporal) and place (spatial). The agricultural sector is one of the mainstay sectors driving the economy of Konawe Regency, this can be seen in the area of ​​utilization of the agricultural sector carried out by the community increasing in 2009 reaching 37,442 ha and in 2010 reaching 42,114 ha. The construction of Embung in the Anggotoa watershed area is an alternative in handling the decrease in water discharge in the Konaweeha watershed. In the analysis of effective rainfall (Re) at 3 (three) rain gauge stations is 2.19 mm / day, and the mainstay discharge (R80) is 47 mm / daym using the Weibull Gumbel Method. The average debit of Anggotoa river (Q) is 0.93 m3 / sec or 930 l / sec. the maximum water demand during the tillage period is 1.64 l / sec / ha, the growth period is 1.37 lt / sec and at harvest time is 0.68 l / de / hat. The reservoir capacity of 16,136 m3 to meet the water needs of the entire area of ​​875 ha spread in 3 (three) villages: Analahumbuti Village, Anggotoa Village, Kukuluri Village and 125 ha will be developed in the Kec. Meluhu. Projected population of 2016 to 2026 (in the next ten years), the land / people needs of 0.66 ha will be 4,979 ha